KARYOTYPE AND NUCLEOLUS ORGANIZER REGIONS OF PYRRHULINA CF AUSTRALIS (PISCES, CHARACIFORMES, LEBIASINIDAE) - Oliveira, C.; Andreata, A. A.; Toledo, LFA; Toledo, S. A. (Soc Brasil Genetica, 1991)
The mitotic chromosomes and nucleolus organizer regions (NORs) of the Upper Parana Basin fish Pyrrhulina cf. australis were studied. The karyotype (2n = 40; 6st + 34a) is characterized by the presence of four chromosome pairs with NORs, one of them with NORs in both terminal regions. Comparison of this karyotype with those of other Characiformes, revealed a strong similarity to the family Erythrinidae.